Specific dimensions of leadership in project management - Djhelilova, Rezmie; Islam, Atche (Vilnius University Open Series, 2019)
The report focuses on some specific dimensions of leadership in project management. Consideration is given to a set of factors that influence effective leadership in the project team. It is pointed out that in an environment of uncertainty and complexity, more and more organizations are moving towards a team approach for implementing project activities, thus striving to overcome the challenges of the environment in which they operate. In project management, leadership must take into account the current situation of the organization implementing the project. The most important task of the leaders in the field of project management is to achieve results. Leadership in project management can also be seen as a function of circumstance and the result of the interaction between members of the team who appoint a representative to organise a project and achieve its objectives.